Prediction of Post-Stroke Depression with Combined Blood Biomarkers IL-6, TNF-α, and Fatty Acid Binding Protein: A Prospective Study: Biomarkers predict post-stroke depression - Wang, Linlin; Chen, Chunyou; Zhu, Jingang; Bao, Xianjun; Tao, Xiaoxiao (Journal of Medical Biochemistry, 2023)
Background: To investigate the expression levels of blood biomarkers interleukin-6 (IL-6), tumor necrosis factor (TNF-α), and intestinal fatty acid binding protein (iFABP) in patients with post-stroke depression (PSD), and their correlation with PSD occurrence. Methods: Clinical data of stroke patients admitted to the First People’s Hospital of Wenling from December 2017 to December 2022 were retrospectively analyzed. Patients were classified into two groups based on their Hamilton Depression Rating Scale (HAMD) scores: PSD and non-PSD groups. The blood levels of IL-6, TNF-α, and iFABP were compared between the two groups, and their association with PSD occurrence was analyzed. Results: The PSD group had significantly higher levels of IL-6, TNF-α, and iFABP. The combined detection of these biomarkers demonstrated a greater predictive value for PSD occurrence compared to the individual detection of each biomarker. Conclusion: The study indicates that the levels of IL-6, TNF-α, and iFABP in the blood are significantly increased in patients with PSD. The combined detection of these biomarkers can effectively predict the occurrence of PSD, indicating high clinical value.
Keywords: Post-stroke depression; Intestinal fatty acid binding protein; IL-6; TNF-α